Biological soil crusts as a major ecosystem component in sandization areas of the Brazilian Pampa - Webber, Carla L.; Bremer, Ulisses F.; Taghizadeh-Mehrjardi, Ruhollah; Weber, Bettina; Rosa, Aline; Scholten, Thomas; Seitz, Steffen (Geoderma Regional, 2023)
In the Brazilian Pampa, vegetation disturbance and soil degradation led to an expansion of sediment remobilization areas, a process locally termed as sandization. Transported sands generate severe environmental problems and hamper the growth of vegetation. However, parts of these sandization areas are quickly covered by biological soil crusts (biocrusts), which have not been investigated in this biome before. This study describes biocrust occurence in sandization areas of the Brazilian Pampa for the first time and analyses their distribution patterns related to the local topography. We studied biocrusts at two research sites where their presence appeared to be essential for soil protection. First, the occurrence of different biocrust types were assessed and a taxonomic survey was conducted. Second, UAV-based imagery was created and biocrusts were classified, using a random forest approach to understand the relation of their abundance to topography. We observed that biocrusts occurred widely in areas prone to sandization with an approx. 25% distribution on the land surface. They are mostly dominated by cyanobacteria and secondarily by bryophytes. Among the observed genera, the cyanobacterial genus Stigonema sp. was dominating in both study sites. Campylopus pilifer was the dominating moss species. The mapped biocrusts represented all major morphological types and were classified as rolling, pinnacled, rugose, and smooth crusts. Local topography was a major driver for biocrust distribution, but also the establishment of vascular plants. Slope and aspect had a strong influence on biocrust development, but the presence of protective topographic positions against atmospheric influences most prominently facilitated their occurrence. This pilot study proves that biocrusts can potentially play a key role as ecosystem engineers in the Brazilian Pampa with a positive effect on general vegetation growth and soil-stabilization. In this biome, however, they have been largely overlooked compared to other areas globally. Thus, biocrusts need to be further studied and their effects considered in land management to constrain further soil degradation. •Biocrusts are highly abundant in sandization areas within the subtropical Brazilian Pampa.•Here, they show the potential to serve as important ecosystem engineers in areas subject to excessive sediment mobilization.•Local topography appeared to be a major driver for biocrust distribution.•Cyanobacteria-dominated biocrusts were most abundant in the initial stage of vegetation development after disturbance.